THE ROLE AND IMPORTANCE OF STRATEGIC PLANNING IN MARKETING - Xo'jayorova Saodat Obid qizi; Zubaydova Nilufar Negmatullayevna (TADQIQOTLAR.UZ, 2024)
Abstract.  Marketing  strategy  is  the  marketing  of  a  firm’s  target  market  is  a master program that represents the activities of the company and includes the process of  achieving its  goals through the development and implementation  of  a long-term marketing  mix  (marketing  mix).  Separate  product,  pricing,  distribution,  sales  and communication policies are defined for each segment of the market. The marketing strategy determines which product (service) the firm should enter, which market, and when. The following marketing strategies have been tested and successfully used by companies in the world market practice.